2020
DOI: 10.1111/nhs.12705
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent sexism of nursing students in Turkey and South Korea: A cross‐cultural comparison study

Abstract: Culture has become increasingly important concepts in nursing in the era of globalization. Nurses' cultural biases and prejudices are huge obstacles to their caring for patients from diverse cultural backgrounds. Therefore, this study examined sexism among nursing students from two patriarchal societies: Turkey influenced by Islam, and South Korea influenced by Confucianism. For this comparative study, we used the survey data from the sample of 560 nursing students, 309 from Turkey and 251 from South Korea. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…A previous study on nurses [1] showed that male nurses perceived managerial roles in nursing professions according to gender stereotypes; more specifically, they associated managerial roles more closely with men than women compared to female nurses. Moreover, in a previous study in Turkey and Korea, two countries with patriarchal cultures [14], male nursing students showed more sexist attitudes than female nursing students. Such gender stereotyping suggests the possibility of another form of gender segregation and that medical institutions should ensure gender equality in managerial roles.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A previous study on nurses [1] showed that male nurses perceived managerial roles in nursing professions according to gender stereotypes; more specifically, they associated managerial roles more closely with men than women compared to female nurses. Moreover, in a previous study in Turkey and Korea, two countries with patriarchal cultures [14], male nursing students showed more sexist attitudes than female nursing students. Such gender stereotyping suggests the possibility of another form of gender segregation and that medical institutions should ensure gender equality in managerial roles.…”
Section: Discussionmentioning
confidence: 85%
“…In the era of globalization, culture is an essential concept in nursing [14]. Traditionally, Korea has been under the influence of Confucianism with moral and philosophical rather than religious meanings [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aligns with the other findings of this study regarding stereotypes about men and the stereotypical perception that nursing is a female job. Korea has been strongly influenced by Confucianism, in which the patriarchal system is deeply rooted, and men who choose jobs perceived as "females' jobs" tend to be stigmatized, and doing so is seen as taboo [37]. This social prejudice has also been reported as an issue in other Asian countries [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…[8] çalışmasında, sağlık yüksekokulu kadın öğrencilerinde korumacı cinsiyetçilik puan ortalaması çalışmamızdan daha düşük bulunmuştur. Tekkaş ve ark., [24] çalışmalarında 309 hemşirelik öğrencisi ile yaptıkları analizde öğrencilerin korumacı cinsiyetçilik alt boyutundan aldıkları puanların eğitim süresi uzadıkça düştüğünü saptamışlardır. ÇDCÖ ile MTÖ puanları arasındaki ilişki incelendiğinde; ÇDCÖ alt boyutları ile MTÖ toplam puanları arasında istatistiksel olarak anlamlı bir korelasyon bulunmamıştır (p>.05).…”
Section: Discussionunclassified